Planning and Organising Protection of Critical Infrastructure - Barć, Marek (Polityka i Społeczeństwo, 2022)
The article is devoted to planning and organizing critical infrastructure protection. The planning method was indicated there, and the layout of the critical infrastructure protection plan was presented. The most important thing is to protect critical infrastructure components that citizens use on a daily basis. So I am talking in the article about energy supply systems, energy resources and fuels, food and water supply system. And above all about financial systems, healthcare and ICT.